2011
DOI: 10.1093/geront/gnr022
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of At-Homeness and Health in Usual Care and Small House Nursing Homes

Abstract: This study demonstrates that a "one size fits all" approach may not be best because at-homeness is an individualized construct. Complex relationships emerged between perceived self-care ability, functional performance, and SmH nursing homes. Mixed methods enable deeper understanding of therapeutic environments and inform the development and testing of tailored interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 16 publications
1
63
0
2
Order By: Relevance
“…This is a reasonably direct and discernible cause–effect mechanism. It is surprising, then, that the perceived autonomy the private flats offered to the residents did not appear as a factor influencing residential satisfaction in the small-house nursing homes in Molony and colleagues’ study (2011), although it affected at-homeness. The fact that perceived autonomy in conventional nursing homes in the same study was not linked to residential satisfaction is less surprising if the care needs of the residents are taken into account.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…This is a reasonably direct and discernible cause–effect mechanism. It is surprising, then, that the perceived autonomy the private flats offered to the residents did not appear as a factor influencing residential satisfaction in the small-house nursing homes in Molony and colleagues’ study (2011), although it affected at-homeness. The fact that perceived autonomy in conventional nursing homes in the same study was not linked to residential satisfaction is less surprising if the care needs of the residents are taken into account.…”
Section: Discussionmentioning
confidence: 83%
“…This somewhat surprising result, which contradicts the results of Kane and colleagues (2007), points to the importance of the co-constitution of care/space. Molony and colleagues’ study (2011) also showed strong resident preferences for the physical environment in the small-house nursing home. In particular, the single rooms were highly appreciated compared with the shared rooms in the conventional nursing home.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations